THE EXTERNALITIES OF GOLD MINING COMPANIES (A CASE STUDY OF PT AGINCOURT RESOURCES IN SOUTH TAPANULI) - Indra Mualim Hasibuan; Ridho Erianto; Isnaini Harahap (Proceeding International Seminar of Islamic Studies, 2023)
Indonesia is blessed with a wealth of natural resources in the mining sector.  Mining activities are often controversial because they are seen as problem makers. Whereas in reality mining company do not always provide negative externalities, but can provide positive externalities in the social, economic and environmental sectors.  The purpose of this research is to examine how the positive externalities of PT Agincourt Resources in South Tapanuli Regency, in terms of the social, economic and environmental sectors.  The research method is qualitative research with a literature study approach. Data collection techniques using documentation techniques. Data analysis uses source triangulation technique. The results of the study, First, in the social sector, company provide positive externalities, such as in the health sector, company routinely carry out free cataract operations, in the education and infrastructure sector, company build library buildings, school infrastructure, bridges and community tours. Second, in the economic sector the company prioritizes local communities as company employees, the company also provides free job training. Third, in the environmental sector, the company is committed to preserving the environment by planting trees every year, and the company is committed to preserving the Batang Toru river.